AN ANALYSIS OF NARRATIVE TECHNIQUES IN BAMA’S KARUKKU - Mr. Saju Jose Kannalil, Dr. R. Shanth (South Eastern European Journal of Public Health, 2025)
The fragmented structure, oral storytelling customs, and the interaction between individual and collective narratives are the main topics of this study's analysis of the narrative strategies used in Bama's Karukku. The examination looks at how these methods give Dalit literature validity while upending traditional literary structures. The problem identification, literature evaluation, methodology, analysis, and conclusion are all part of the research's structured approach. By closely examining Karukku, this study demonstrates how Bama's distinctive storytelling approach amplifies the impact of her socio-political critique, ultimately adding to the larger conversation about religious discrimination, gender injustice, and caste oppression.